Volume 7: Turbomachinery, Parts A, B, and C 2010
DOI: 10.1115/gt2010-22581
|View full text |Cite
|
Sign up to set email alerts
|

Stability Improvement of High-Pressure-Ratio Turbocharger Centrifugal Compressor by Asymmetric Flow Control: Part I—Non-Axisymmetric Flow in Centrifugal Compressor

Abstract: This is the Part I of a two-part paper documenting the development of a novel asymmetric flow control method to improve the stability of a high-pressure-ratio turbocharger centrifugal compressor. Part I focuses on the non-axisymmetric flow in a centrifugal compressor induced by the non-axisymmetric geometry of the volute while Part II describes the development of asymmetric flow control method to avoid the stall on the basis of the characteristic of non-axisymmetric flow. To understand the asymmetries, experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…This phenomenon has long been recognized in both experiments and numerical simulations, [1][2][3] and its effects on the performance of centrifugal compressors were widely studied. [4][5][6] The experiments and numerical simulations conducted by Yang et al 4 confirmed that the pressure distortion induced by the volute extended upstream to the impeller inlet, implying that the impeller was subjected to varying inlet and exit conditions, which led to the deterioration of the performance. Zheng et al 5 compared performance of a high pressureratio centrifugal compressor with and without the volute using three-dimensional viscous computational fluid dynamics (CFD).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…This phenomenon has long been recognized in both experiments and numerical simulations, [1][2][3] and its effects on the performance of centrifugal compressors were widely studied. [4][5][6] The experiments and numerical simulations conducted by Yang et al 4 confirmed that the pressure distortion induced by the volute extended upstream to the impeller inlet, implying that the impeller was subjected to varying inlet and exit conditions, which led to the deterioration of the performance. Zheng et al 5 compared performance of a high pressureratio centrifugal compressor with and without the volute using three-dimensional viscous computational fluid dynamics (CFD).…”
Section: Introductionmentioning
confidence: 91%
“…Yang et al 4 compared the static pressure distribution in the vaneless diffuser and the impeller captured by steady simulation with frozen-rotor method and S-A model, and experimental measurements, as shown in Figure 5. It can be seen that the steady simulation with ''frozen-rotor method'' well predicted the phase (location of the minimum) and the magnitude of the static pressure distribution at the impeller outlet ( Figure 5(a)), as well as the magnitude of the static pressure distribution within the impeller ( Figure 5(b)).…”
Section: Prototypementioning
confidence: 99%
See 1 more Smart Citation
“…In other words, the inlet pressure and outlet pressure of the compressor could reflect compressor performance, to a certain extent. In order to investigate the relationship between the compressor pressure and performance, the study of the compressor requires massive numerical simulations and experiments [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The asymmetric volute is usually designed as a spiral-shaped overhung housing that acts as a diffuser at lower flow rates but as a nozzle at higher flow rates than the design values. This situation causes an asymmetric pressure distribution in the diffuser exit, which has a significant impact on the upstream components 3133 and even on the impeller by reducing the performance, particularly in the stable flow range. Zheng et al 34 reported numerical estimations of the impact of the asymmetric volute on the stability of a turbocharger centrifugal compressor with a vaneless diffuser and found that the stable flow range was constricted by up to 42% at the design speed, indicating that the volute harms the flow stability severely.…”
Section: Introductionmentioning
confidence: 99%